Optimal Multiobjective Control of Low-Voltage AC Microgrids: Power Flow Regulation and Compensation of Reactive Power and Unbalance - Brandao, Danilo; Ferreira, Willian M.; Alonso, Augusto M. S. [UNESP]; Tedeschi, Elisabetta; Marafao, Fernando P. [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2020)
The presence of single-phase distributed generators unevenly injecting active power in three-phase microgrids may create undesired upstream current unbalance. Consequently, voltage asymmetry and even active power curtailment may occur in such networks with negative economic impact. Thus, this paper proposes an optimal multiobjective approach to regulate the active and reactive power delivered by distributed generators driven by a three-layer hierarchical control technique in low-voltage microgrids. This method does not require previous knowledge of network parameters. The multiobjective algorithm is implemented in the secondary level achieving optimal dispatch in terms of maximizing the active power generation, as well as minimizing the reactive power circulation and current unbalance. By the existence of a utility interface three-phase converter placed at the point-of-common-coupling, the proposed control can regulate the power circulating among the microgrid phases, and the microgrid structure can withstand grid-connected and islanded operating modes. The path for interphase power circulation through the DC-link of the utility interface allows the multiobjective algorithm to achieve better results in terms of generation and compensation compared to the system without utility interface. The proposed method is assessed herein by computational simulations in a three-phase four-wire microgrid under realistic operational conditions.
Keywords: Reactive power; Voltage control; Load flow; Microgrids; Power generation; Optimization; Inverters; Distributed generation; microgrid; multiobjective; optimization; power quality; unbalance